2017
DOI: 10.1212/nxi.0000000000000320
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of alemtuzumab following fingolimod for multiple sclerosis

Abstract: Objective:To describe a series of patients with relapsing multiple sclerosis (MS) who experienced significant and unexpected disease activity within the first 12 months after switching from fingolimod to alemtuzumab.Methods:Patients with relapsing MS treated sequentially with fingolimod then alemtuzumab who experienced significant subsequent disease activity were identified by personal communication with 6 different European neuroscience centers.Results:Nine patients were identified. Median disease duration to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 10 publications
1
50
0
2
Order By: Relevance
“…Alternatively it has also been suggested that prior use of fingolimod, to sequester lymphocytes into lymphoid tissue and bone marrow, may block the activity of alemtuzumab and allow more rapid repopulation . Therefore, it is of interest that one of the poor depleters reported here was treated with fingolimod prior to alemtuzumab.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Alternatively it has also been suggested that prior use of fingolimod, to sequester lymphocytes into lymphoid tissue and bone marrow, may block the activity of alemtuzumab and allow more rapid repopulation . Therefore, it is of interest that one of the poor depleters reported here was treated with fingolimod prior to alemtuzumab.…”
Section: Discussionmentioning
confidence: 93%
“…Two people depleted by < 50% after first administration, although one of these was lymphopenic at baseline. Of note, the individual who was a poor‐depleter (11·1%) had been treated with fingolimod, a risk factor for lack of alemtuzumab activity, before switching to alemtuzumab. However other individuals were identified who depleted very poorly upon the first infusion, but had not used fingolimod previously.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Неврология, нейропсихиатрия, психосоматика. 2019;11(3): [16][17][18][19][20][21][22][23][24][25] К Л И Н И Ч Е С К И Е Р Е К О М Е Н Д А Ц И И Таблица 3. Мониторирование уровня CD19-лимфоцитов в рутинной клинической практике не является обязательным, так как не влияет на график введения препарата.…”
unclassified
“…Willis et al 2 describe 9 patients with relapsing MS treated sequentially with fingolimod and alemtuzumab, who developed substantial and unanticipated disease activity after starting alemtuzumab. In 8 of 9 patients, the disease activity included at least one clinical relapse in the first 12 months after initiating alemtuzumab, and all patients had MRI evidence of new disease activity.…”
mentioning
confidence: 99%